2016
DOI: 10.3389/fpls.2016.01082
|View full text |Cite
|
Sign up to set email alerts
|

GmCLC1 Confers Enhanced Salt Tolerance through Regulating Chloride Accumulation in Soybean

Abstract: The family of chloride channel proteins that mediate Cl- transportation play vital roles in plant nutrient supply, cellular action potential and turgor pressure adjustment, stomatal movement, hormone signal recognition and transduction, Cl- homeostasis, and abiotic and biotic stress tolerance. The anionic toxicity, mainly caused by chloride ions (Cl-), on plants under salt stress remains poorly understood. In this work, we investigated the function of soybean Cl-/H+ antiporter GmCLC1 under salt stress in trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 36 publications
3
69
0
Order By: Relevance
“…However, with increasing salt stress treatment time, the marginal expression of HKT1:1genemay regulate the retrevial of Na + from the xylem (Davenport et al, 2007; Ali et al, 2016). The expression levels of CLC1 indicates that CLC1 may not be involved in the Cl - vacuolar sequestation (Wei et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, with increasing salt stress treatment time, the marginal expression of HKT1:1genemay regulate the retrevial of Na + from the xylem (Davenport et al, 2007; Ali et al, 2016). The expression levels of CLC1 indicates that CLC1 may not be involved in the Cl - vacuolar sequestation (Wei et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…AtCLCg is a unique protein that mediates Cl − compartmentalization into vacuoles of mesophyll cells in Arabidopsis [33]. In the typical Cl − -sensitive plant Glycine max, GmCLC1, a homolog of AtCLCg is preferentially expressed at the tonoplast of root cells, and thus the main function of GmCLC1 is to withhold Cl − in roots to decrease Cl − accumulation in shoots [34]. In the present study, the transcript abundance of P. cornutum CLCg in shoots was enhanced under salt treatment at both 6 and 24 h, as seen in Table 3.…”
Section: The Possible Molecular Basis Underlying CL − Transport In Thmentioning
confidence: 99%
“…Numerous transgenic studies have suggested that SOS1 as a Na + efflux transporter may be considered as the most important functional protein for the acquirement of a salt tolerance trait for different plant species (Nie et al, 2015). Cluptake, transport and compartmentation are mediated by chloride channels (CLCs), which are mostly distributed in the tonoplast of cell vacuoles, for soybean as an example, Gm-CLC1 has been shown to locate at the tonoplast and play a crucial role for Cluptake and compartmentation in the vesicles and for Cl -/salt tolerance under saline conditions (Wong et al, 2013;Wei et al, 2016). A widely studied chlorophyll derivative, chlorophyllin (CHL), the sodium-copper salt and water-soluble analogue of the ubiquitous green pigment chlorophyll, has been shown to possesses higher antioxidant ability than AsA, GSH, mannitol, and tert-butanol at equimolar concentrations for protecting mitochondria, inhibiting the mutagenicity of various chemicals in bacteria or mice (Kamat et al, 2000).…”
Section: Introductionmentioning
confidence: 99%